Investigating the mediating role of job embeddedness: evidence of Iranian context. Issue 3 (20th March 2019) - Rahimnia, Fariborz; Eslami, Ghasem; Nosrati, Saeid
Abstract : Purpose: The purpose of this paper is to investigate the mediating role of job embeddedness in the relationship between perceived job security and perceived job flexibility and its impact on creative performance. Design/methodology/approach: The statistical population of this study consisted of all employees at the Electricity Company of Mashhad, and a sample comprising 300 participants was finalized. In order to analyze the data, different statistical analysis methods were used, including Pearson's correlation analysis and structural equation modeling. Findings: The findings indicated that perceived job security has a positive impact on job embeddedness, while it has no significant impact on the employees' creative performance. On the other hand, perceived job flexibility has a positive effect on both job embeddedness and creative performance. Moreover, the mediating role of job embeddedness was approved. Originality/value: Since creative performance in this changeable environment becomes essential, identifying mechanisms which can embed employees to their company would bring about several positive consequences. Furthermore, little is known about the antecedents and potential consequences of job embeddedness, especially in developing countries.